2011
DOI: 10.1111/j.1365-2044.2011.06784.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hypothermia and patient outcomes after elective cardiac surgery

Abstract: Summary Hypothermia after elective cardiac surgery is an important physiological abnormality and is associated with increased morbidity and mortality. The Australian and New Zealand intensive care adult patient database was studied to obtain the lowest and highest temperature in the first 24 h after surgery. Hypothermia was defined as core temperature < 36 °C; transient hypothermia as temperature < 36 °C that was corrected within 24 h; and persistent hypothermia as hypothermia that was not corrected within 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 29 publications
1
36
0
4
Order By: Relevance
“…Perioperative hypothermia may be a confounder as it is associated with decreased BIS values during cardiopulmonary bypass and increased cardiac morbidity, coagulation dysfunction, and mortality. 2832 This study identified a positive association between temperatures and BIS values while patients were not on cardiopulmonary bypass. However, the lack of association between temperature and postoperative mortality may be due to the fact that there were relatively few epochs of severe hypothermia.…”
Section: Discussionmentioning
confidence: 78%
“…Perioperative hypothermia may be a confounder as it is associated with decreased BIS values during cardiopulmonary bypass and increased cardiac morbidity, coagulation dysfunction, and mortality. 2832 This study identified a positive association between temperatures and BIS values while patients were not on cardiopulmonary bypass. However, the lack of association between temperature and postoperative mortality may be due to the fact that there were relatively few epochs of severe hypothermia.…”
Section: Discussionmentioning
confidence: 78%
“…We planned to over-enrol by 20% to account for losses to follow-up (10% study attrition [15]; 10% mortality at six-months post-hospital discharge following a critical illness) [1,29]. The total planned recruitment was therefore 240.…”
Section: Methodsmentioning
confidence: 99%
“…A critical illness requiring admission to a general intensive care unit (ICU) affects approximately 119,000 adult Australians per year [1]. While survival rates approximate 89% at hospital discharge [2], functional recovery for individuals is delayed often beyond six months post-discharge [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the article by Karalapillai et al [1]. As the authors pointed out, the study's strength lies in its large size and integration of data from multiple centres.…”
Section: Postoperative Hypothermia and Outcomes After Cardiac Surgerymentioning
confidence: 99%
“…A recent National Patient Safety Agency release has emphasised the importance of reliable and available airway suction equipment [1]. A common method of providing suction within the operating theatre is via a centralised vacuum system, comprising a pump, receiver and filter [2,3].…”
Section: Is It Good To Share? Suction Splitters In Operating Theatresmentioning
confidence: 99%